Karakteristik Tari Zapin Setapak Sebagai Bentuk Tari Kreasi di Sanggar Citra Art Studio - Sheila Diani Jaya; Ida Bagus Ketut Sudiasa; Ojang Cahyadi (Jurnal Pendidikan Tari, 2025)
This study aims to describe the form of presentation of the Zapin Setapak dance in the Citra Art Studio studio. This study uses a qualitative approach with descriptive and analytical research types. The subjects in this study were the studio leader, choreographer and music composer in the Zapin Setapak dance. Data collection in this study was through observation, interview, and documentation techniques. The results of this study indicate that the Zapin Setapak Dance is a manifestation of the development of the Malay Zapin dance, as evidenced by the Citra Art Studio Studio with the owner Siti Suryani, located in the DKI Jakarta area, creating a creative Zapin Setapak dance with characteristics that have their own uniqueness and characteristics by using movements that emphasize the movements of zapin, joget, silat, and are inseparable from the touch of basic Malay motif movements with a distinctive and thick taste. This study is interpreted by Soedarsono's theory on characteristics as a form of creative dance, so that in the Zapin Setapak Dance it can provide deep insight into various elements of dance, from movement to cultural meaning.